1994
DOI: 10.1111/j.1365-3121.1994.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate‐related river activity at the Weichselian‐Holocene transition: a comparative study of the Warta and Maas rivers

Abstract: Huvial systems from the Dutch and Polish lowlands are compared for their evolution during the Weichselian deglaciation period. In both regions the Pleniglacial braided-river pattern changed to a meandering pattern in the beginning of the Lateglacial. Several transitional stages between braided and high-sinuosity meandering systems have been recognized. A difference in fluvial activity is found during the Younger Dryas when the Maas transformed to a braided pattern while the Warta maintained its meandering patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
1
8

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 0 publications
8
104
1
8
Order By: Relevance
“…As a re sult, sed i men ta tion pre vailed over in ci sion in the inter gla cial val ley. Our find ing matches con clu sions drawn by Vandenberghe et al (1994) and Krzyszkowski (1996) that the Qua ter nary me an der ing tem per ate flu vial sys tems were aggradational ones.…”
Section: Erosion and Aggradation Phases During The Glacial-interglacisupporting
confidence: 87%
See 1 more Smart Citation
“…As a re sult, sed i men ta tion pre vailed over in ci sion in the inter gla cial val ley. Our find ing matches con clu sions drawn by Vandenberghe et al (1994) and Krzyszkowski (1996) that the Qua ter nary me an der ing tem per ate flu vial sys tems were aggradational ones.…”
Section: Erosion and Aggradation Phases During The Glacial-interglacisupporting
confidence: 87%
“…Such fluvial sed i men tary re cords have been rec og nized in de tail in the Neth er lands (Van Huissteden, 1990;Kasse et al, 1995;Weerts and Berendsen, 1995;Huisink, 2000;Mol et al, 2000;Busschers et al, 2007;Hijma and Co hen, 2011), the Brit ish Isles (Brown, 1995;Rose, 1995;Col lins et al, 1996;Gao et al, 2007), Ger many (Mol, 1995(Mol, , 1997Mol et al, 2000;Andres et al, 2001;Dambeck and Thiemeyer, 2002;Kasse et al, 2003;Erkens et al, 2011), north ern France (Lefevre et al, 1995;Straffin et al, 2000;Antoine et al, 2003) and in Po land (Szumañski, 1983;Rotnicki, 1987;Kozarski et al, 1988;Turkowska, 1988;Vandenberghe et al, 1994;Kalicki, 1996;Florek, 1997;Starkel, 2002;Starkel et al, 2007;Gêbica, 2004). Sev eral stud ies have been con ducted in East ern Eu rope as well, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There are counterexamples of European valleys, however, that did not see a braidplain re-establish. For example, the Warta in Poland (Vandenberghe et al, 1994), the Scheldt in Belgium (Kiden, 1991) and the Tisza in Hungary (Kasse et al, 2010). The Rhine has examples of both these behaviours.…”
Section: Younger Dryasmentioning
confidence: 99%
“…The increase in detrital sedimentation ( [Rose, 1995], [Pastre et al, 1997], [Pastre et al, 2003], [Andres et al, 2001], [Antoine et al, 2003] and [Orth et al, 2004]) and the aeolian deposits interbedded in fluvial sediments ( [Haesaerts, 1984] and [van Huissteden et al, 1986]; [Vandenberghe et al, 1987] and [Mol et al, 2000]) observed during the Younger Dryas in more northern areas are not found in the Choisille catchment. Moreover, there is no evidence of the changes in river patterns suggested in the south-western Parisian Basin after the Allerød (Visset et al, 2005) or during the LateGlacial-Holocene transition , as testified in numerous sites in the Parisian Basin ( [Pastre et al, 1997], [Antoine et al, 2003] and [Orth et al, 2004]) and northwestern Europe ( [Vandenberghe et al, 1994] and [Mol et al, 2000]). The channel patterns inherited from phase 4 continued with no significant change throughout the Choisille floodplain (Fig.…”
Section: Fluvial-system Reactivity To the Forcing Factors And Specifimentioning
confidence: 99%
“…[Macklin and Needham, 1992], [Bohncke, 1993], and [Visset et al, 2005]). They can be used to study the palaeohydrological and morpho-sedimentary evolution of rivers in relation to palaeoenvironmental changes, for example during the LateGlacial (e.g., [Haesaerts, 1984], [Vandenberghe et al, 1994], [Rose, 1995], [Antoine, 1997], [Antoine et al, 2003], [Pastre et al, 2002a] and [Pastre et al, 2003]). They also demonstrate the extensive development of silty sedimentation and hydro-sedimentary disturbances due to human activities during the last millenia (e.g.…”
Section: Introductionmentioning
confidence: 99%